ANALISIS STRUKTUR RETORIKA DAN FITUR LINGUISTIK BAGIAN PENDAHULUAN ARTIKEL JURNAL PENELITIAN BERBAHASA INDONESIA DALAM BIDANG ILMU KEDOKTERAN DAN KESEHATAN - Sepni, Lexpya (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
The purpose of this study was to describe the structure of the rhetoric of the introductory part of the research journal articles in Indonesian language. Linguistic features the introduction Indonesian language research journal articles in the field of medical science and health. This research uses descriptive method. Source of this research are 50 articles while the data in the form of research journal articles in the field of medical science and health. Data collection techniques are documents such as speech writer in the text of the discourse, data analysis techniques to read and memberian code of the article, the findings of this study analyzed the structure of rhetoric uses the theory of MMP which consists of 4 stages and 18 steps, while the feature linguistics is defined as the use of the type or variety text associated with active and passive sentences, types of clauses, conjunctions / circuit. The research result rhetorical structure analysis introductory part AJP in the field of medicine and health, such as the use of the stages and steps are found or used in a rhetorical structure AJP field of medical science and health with the result that most of the stages of T-2 to justify the research topic. While the use measures in stages in the field of medicine and health: (1) step T2-LC merefiu related literature, (2) a step T1-LD describe lok ation of geographic research, (3) a step T4-LA explain the purpose of the study, which the last (fourth) step T3-LD expressed interested in examining the issue. Furthermore, linguistic features found in the introductory part of AJP in the field of medical science and health, among others: (1) active and passive sentences, (2) coordination, (3) the subordinate attributes.